Coaching and Mentoring: Theory and Practice - Paul Stokes; Robert Garvey (UK SAGE Publications Ltd, 2022)
Written by two leading scholars in the field, this book is an essential guide to the theory and practice of coaching and mentoring. The 4th Edition features: - New content on the definitional issues and the hybridization of coaching and mentoring - Revised analysis on the research terrain of coaching and mentoring - Careful consideration of the impacts of the Covid-19 pandemic on coaching and mentoring - New and updated case studies and examples from a wide range of countries, including the USA, Africa, Saudi Arabia, Hong Kong, Russia, Australia, South America, the Czech Republic and Sri Lanka - Updated activities, reflective questions and annotated further reading at the end of each chapter This book also comes with an Instructor's Manual and PowerPoint slides for lecturers to use in their teaching. Suitable reading for students on coaching and mentoring modules.
Keywords: Nonfiction; Textbooks; Coaching; Mentoring; Leadership and Mentoring (HRM2073-N)